2022
DOI: 10.1016/j.crad.2021.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Parenchymal involvement on CT pulmonary angiography in SARS-CoV-2 Alpha variant infection and correlation of COVID-19 CT severity score with clinical disease severity and short-term prognosis in a UK cohort

Abstract: To determine if there is a difference in radiological, biochemical, or clinical severity between patients infected with Alpha-variant SARS-CoV-2 compared with those infected with pre-existing strains, and to determine if the computed tomography (CT) severity score (CTSS) for COVID-19 pneumonitis correlates with clinical severity and can prognosticate outcomes.MATERIALS AND METHODS: Blinded CTSS scoring was applied to 137 hospital patients who had undergone both CT pulmonary angiography (CTPA) and whole-genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…In contrast, there was no significant radiological difference between wild type and Alpha variant. This was also consistent with a previous report from the UK that compared the chest CT findings of these subtypes [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In contrast, there was no significant radiological difference between wild type and Alpha variant. This was also consistent with a previous report from the UK that compared the chest CT findings of these subtypes [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, there was no significant radiological difference between wild type and Alpha variant. This was Data are shown as absolute numbers (percentage), mean ± standard deviation GGO Ground-glass opacity, w a One-way analysis of variance b Pearson χ 2 test or Fisher's exact test c Bonferroni corrected p = 0.06 for wild type vs. Alpha variant, Bonferroni corrected p = 0.1 for wild type vs. Delta variant, and Bonferroni corrected p = 1.0 for Alpha variant vs. Delta variant d Bonferroni corrected p = 1.0 for wild type vs. Alpha variant, Bonferroni corrected p = 0.012 for wild type vs. Delta variant, and Bonferroni corrected p = 0.003 for Alpha variant vs. Delta variant e Bonferroni corrected p = 0.8 for wild type vs. Alpha variant, Bonferroni corrected p = 0.3 for wild type vs. Delta variant, and Bonferroni corrected p = 0.033 for Alpha variant vs. Delta variant f Bonferroni corrected p = 1.0 for wild type vs. Alpha variant, Bonferroni corrected p = 0.003 for wild type vs. Delta variant, and Bonferroni corrected p < 0.001 for Alpha variant vs. also consistent with a previous report from the UK that compared the chest CT findings of these subtypes [8]. This study is subject to limitations and challenges.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Multiple studies have shown the degree of parenchymal involvement on CT imaging to associate with disease severity and poor hospital outcomes, including a study that used a 25-point chest CT severity score (CT-SS) of CT pulmonary angiograms 6 . Further studies have evaluated the CT imaging characteristics or ‘signature’ of SARS-COV-2 infection 7 , 8 , but studies evaluating the lung imaging findings of Omicron infection versus non-Omicron variants remain lacking.…”
Section: Introductionmentioning
confidence: 99%